Assessment of factors responsible for early menopause in Interior Sindh, Pakistan - LatafatAliChughtai,AlizaSahito,JawaidAhmedZai,ZaibunisaMughal,JamshedWarsi,BenazirMahar, LatafatAliChughtai,AlizaSahito,JawaidAhmedZai,ZaibunisaMughal,JamshedWarsi,BenazirMahar (Journal of Rawalpindi Medical College, 2020)
Objective: To evaluate the factors leading to the early onset of menopause (<40 years) in the women in the interior of Sindh. Materials and Methods: A cross-sectional study was conducted on 218 individuals among them 109 were postmenopausal women (with premature menopause) and 109 were normal menstruating females during the period of six months from November 2014 to April 2015, data was obtained from Interior Sindh, Larkana, Hyderabad, and Benazirabad. Factors considered were age, number of children, history of the obstetric process (ovarian and uterine), diseases, and premature menopause history in first-cousin marriages. The questionnaire data and blood samples were collected for hormonal assays such as LH, prolactin, and FSH. The hormone levels were analyzed by ELISA method, SPSS version 17 was used for data analysis. Results: Out of 109 subjects the percentage of early menopause due to: anorexia nervosa was 17%, brain tumor 7%, ovarian cancer 6%, hormonal disorders 23%, hysterectomy 15%, oophorectomy 5%, Pituitary gland dysfunction 4%, Sheehan Syndrome 24%, Polycystic Ovarian Syndrome (PCOS) 8%. Conclusion: Early menopause was found related to pathological and psychological factors including brain tumor, ovarian cancer, family history, Anorexia nervosa, and certain surgical interventions.